Dissimilatory Metal Reduction by the Facultative Anaerobe Pantoea agglomerans SP1 - Francis, Chris A. (American Society for Microbiology, 2000)
Anaerobic enrichments with acetate as the electron donor and Fe(III) as the terminal electron acceptor were obtained from sediments of Salt Pond, a coastal marine basin near Woods Hole, Mass. A pure culture of a facultatively anaerobic Fe(III) reducer was isolated, and 16S rRNA analysis demonstrated that this organism was most closely related to Pantoea (formerly Enterobacter) agglomerans, a member of the family Enterobacteriaceae within the gamma subdivision of the Proteobacteria. This organism, designated strain SP1, can grow by coupling the oxidation of acetate or H(2) to the reduction of a variety of electron acceptors, including Fe(III), Mn(IV), Cr(VI), and the humic substance analog 2,6-anthraquinone disulfonate, but not sulfate. To our knowledge, this is the first mesophilic facultative anaerobe reported to couple acetate oxidation to dissimilatory metal reduction.